Pengaruh Suhu Pre-Heat Friction Welding Terhadap Sifat Mekanis dan Morfologi Baja AISI 201 - warso; Sutarno; Rivkih amanulloh; Azis satria firmansyah (Accurate: Journal of Mechanical Engineering and Science, 2022)
This study aims to determine the mechanical and morphological properties of AISI 201 Steel Material. The forging pressure is 80 Psi using a rotating speed of 5600 Rpm and the preheat temperature used is 4000C, 5000C, 6000C. The method in this research is descriptive method. The test results produce an average tensile stress of 4000C preheat temperature variation of 523.1 N/mm2, 5000C preheat variation of 534.3 N/mm2, 6000C preheat variation of 566.6 N/mm2, and raw material of 696.35 N/mm2. For this reason, the largest average tensile stress in this variation of raw material is 696.35 N/mm² and from the data results obtained the average tensile strain of 4000C preheat variation is 10.83%, 5000C preheat variation is 11.05%, 6000C preheat variation is 11.73%, and raw materials 23.14%. The average bending stress of the 4000C preheat temperature variation is 21.85N/mm2, the 5000C preheat variation is 52.31 N/mm2, the 6000C preheat variation is 53.38 N/mm2, and the raw material is 117.71N/mm2. The results of the largest average tensile stress in this variation of raw material are 117.71N/mm², in the hardness test a value of 294.7 VHN is obtained and the SEM test on the specimen is the best in the HAZ area which is enlarged 5000x, 200x, and 100x, it can be seen that in the The friction welding penetration welding HAZ is completely filled with no weld defects.